Reading promotion: Much more than reading just to read - Sánchez-García, Sandra (Anuario ThinkEPI, 2018)
Reading promotion is one of the traditional activities in libraries, with the aim of presenting reading as a leisure alternative. Taking into account the social commitment of libraries, these promotions should also be a vehicle to train critical and competent readers, something that has been largely forgotten as librarians focus on the playful nature of reading to attract users. Reading promotion activities would benefit by including information about the possibilities that literary texts offer regarding questions that concern us, therefore transforming the promotion of reading into an authentic socio-educational intervention.
Keywords: Reading; Reading promotion; Reading habits; Reading comprehension; Socio-educational intervention.